2012
DOI: 10.1007/s10995-012-1096-6
|View full text |Cite
|
Sign up to set email alerts
|

Social-Emotional Support, Life Satisfaction, and Mental Health on Reproductive Age Women’s Health Utilization, US, 2009

Abstract: To examine the associations among social-emotional support, life satisfaction, and mental health with not having a routine checkup among women of reproductive age in the US, data from the 2009 Behavioral Risk Factor Surveillance System, a population-based telephone survey of health behaviors, were analyzed among reproductive aged (18–44 years) women in the US. Prevalence estimates were calculated for not having a routine checkup in the past year with measures of social-emotional support, life satisfaction, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Conversely, lower perceived mental health was a barrier to participation. The association between poorer mental health and mental health problems with lower usage of preventive services has been reported by other researchers,37 38 and may be due to altered perceptions of the accessibility or organisation of such services 38 39…”
Section: Discussionsupporting
confidence: 52%
“…Conversely, lower perceived mental health was a barrier to participation. The association between poorer mental health and mental health problems with lower usage of preventive services has been reported by other researchers,37 38 and may be due to altered perceptions of the accessibility or organisation of such services 38 39…”
Section: Discussionsupporting
confidence: 52%
“…with scores ranging from 1 (Always) to 5 (Never) [36]. The scale was used to examine emotional support in American Indian women aged 18-44 [37].…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…9,10 Tailored health communications are modified based on patient-specific characteristics to increase relevance to the recipient; 11 this approach has already shown promise among HPV unvaccinated female college students. 8 Since only 65% of American women aged 18-24 years had a routine checkup in 2009, 12 and only 55% of women aged 15-24 accessed sexual and reproductive health services between 2006 and 2010, 13 relying on clinician recommendation is an extremely limited strategy to increase HPV vaccination in this age group. A recent meta-analysis found that tailored computerbased interventions with decision, behavior, and/or emotional support increased sexual health knowledge and self-efficacy of participants.…”
Section: Introductionmentioning
confidence: 99%